Practicing Student Critical Thinking Through Problem Solving and Disscuss (PSD) Learning - Shomad, Abdul; Soetopo, Dhalia (International Journal for Educational and Vocational Studies, 2020)
Critical thinking is the ability to draw conclusions with the right facts and knowledge. Critical thinking is needed in the era of globalization. The low critical thinking skills of students are trained through the PSD learning model. This research was conducted to train students' critical thinking skills with classroom action research methods. The results of the implementation of classroom action research namely in the first cycle of critical thinking skills of students with a score of 61.6% and the second cycle of critical thinking skills of students with a score of 70%. Thus, the application of the PSD model can train students' critical thinking skills with an increase of 8.4%.